Self investments of adolescents and their cognitive development - Daniela Del Boca; Chiara Monfardini; Cheti Nicoletti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
While a large literature has focused on the impact of parental investments on child cognitive development, very little is known about the role of child's own investments. Information on how children invest their time separately from parents is probably little informative for babies and toddlers, but it becomes more and more important in later stages of life, such as adolescence, when children start to take decisions independently. By using the Child Development Supplement of the PSID (Panel Study of Income Dynamics), we model the production of cognitive ability of adolescents and extend the set of inputs to include the child's own time investments. Looking at investments during adolescence, we find that child's investments matter more than mother's investments. On the contrary, looking at investments during childhood, it is the mother's investments that are more important. Our results are obtained accounting for potential unobserved child's and family's endowments and are robust across several specifications and samples, e.g. considering and not considering father's investments and non-intact families.
Keywords: J13; D1; 330